Comparability and reliability of the positive and negative affect scales in the European Social Survey - Sortheix, Florencia M.; Weber, Wiebke (Frontiers in Psychology, 2023)
This study assessed the measurement invariance of positive and negative affect in the European Social Survey (ESS) in 2006 and 2012. We conducted Multi-Group Confirmatory Factor Analysis with an estimator for ordinal data that allowed us to test for threshold invariance. This level of invariance was not tested before for these scales. Our results for a 3-item measure of Positive Affect and a 5-item measure of Negative Affect showed that configural, threshold and metric (loading) and partial scalar (intercept) invariance held across almost all countries and between the two ESS Rounds. Our results provide cross-cultural validity to a broader measure of negative affect than past research using the ESS and examine these scales across more countries than any past study. Besides providing useful results for well-being researchers using the ESS, the present study advances the discussion about diverging analytical choices in invariance testing.